2020
DOI: 10.24036/ekj.v2.i2.a78
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-Modul berbasis Discovery Learning pada Materi Larutan Elektrolit dan Non Elektrolit Kelas X SMA/MA

Abstract: This research aims to develop teaching materials in the form of e-modules that are valid and practical. The type of research used is research and development (RD). The development model used is the 4-D model which includes 4 stages, namely the define, design, develop and disseminate. Research carried out until the development stage, namely the validity and practicality test. The instruments used were validity and practicality sheets. The e-module was validated by 6 validators, while the practicality test was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
2
9
0
1
Order By: Relevance
“…and "worthy" category to be further developed as English learning media. It was in line with research by Arianti & Zainul (2020) that an e-module is feasible for learning and makes it easier for students to understand learning concepts.…”
Section: Nosupporting
confidence: 79%
See 2 more Smart Citations
“…and "worthy" category to be further developed as English learning media. It was in line with research by Arianti & Zainul (2020) that an e-module is feasible for learning and makes it easier for students to understand learning concepts.…”
Section: Nosupporting
confidence: 79%
“…It could be concluded that the e-module was feasible, excellent, and practical for English learning. It is in line with the research conducted by Arianti & Zainul (2020). They obtain that e-module included in the category of valid and practical.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The mobile learning application that will be developed is expected to be able to attract the interest of students while studying [24]. Its because this application is developed according to the characteristics of the media/teaching materials preferred by students, namely having audio and video [6]. can be used for practice questions (concept stabilization), can be used for measuring the mastery of the material to students, can be used anytime and anywhere, and can be used in a state connected to the internet network or not.…”
Section: Mobile Learning Applicationmentioning
confidence: 99%
“…This of course cannot be separated from the obstacles faced by students during learning. Some of the obstacles that students experience during online learning are difficulty in having internet data, unsupported signals [6], not being able to go online at the specified time, difficulty accessing the application/site used and difficult to understand the subject matter [7]. In addition, the teacher also experienced problems when correcting assignments and training/evaluating students during online learning on the material chemistry is the basic laws of chemistry.…”
mentioning
confidence: 99%